Characteristics and Outcomes of 79 Patients with an Insulinoma: A Nationwide Retrospective Study in Finland - Elina Peltola; Päivi Hannula; Heini Huhtala; Saara Metso; Ulla Kiviniemi; Martine Vornanen; Juhani Sand; Johanna Laukkarinen; Mirja Tiikkainen; Camilla Schalin-Jäntti; Johanna Arola; Jukka Sirén; et al. (International Journal of Endocrinology)
Objective. Insulinomas are rare pancreatic tumours. Population-based data on their incidence, clinical picture, diagnosis, and treatment are almost nonexistent. The aim of this study was to clarify these aspects in a nationwide cohort of insulinoma patients diagnosed during three decades. Design and Methods. Retrospective analysis on all adult patients diagnosed with insulinoma in Finland during 1980–2010. Results. Seventy-nine patients were diagnosed with insulinoma over the research period. The median follow-up from diagnosis to last control visit was one (min 0, max 31) year. The incidence increased from 0.5/million/year in the 1980s to 0.9/million/year in the 2000s (p=0.002). The median diagnostic delay was 13 months and did not change over the study period. The mean age at diagnosis was 52 (SD 16) years. The overall imaging sensitivity improved from 39% in the 1980s to 98% in the 2000s (p<0.001). Seventy-one (90%) of the patients underwent surgery with a curative aim, two (3%) had palliative surgery, and 6 (8%) were inoperable. There were no significant differences in the types of surgical procedures between the 1980s, 1990s, and 2000s; tumour enucleations comprised 43% of the operations, distal pancreatic resections 45%, and pancreaticoduodenectomies 12%, over the whole study period. Of the patients who underwent surgery with a curative aim, 89% had a full recovery. Postoperative complications occurred in half of the patients, but postoperative mortality was rare. Conclusions. The incidence of insulinomas has increased during the past three decades. Despite the improved diagnostic options, diagnostic delay has remained unchanged. To shorten the delay, clinicians should be informed and alert to consider the possibility of hypoglycemia and insulinoma, when symptomatic attacks are investigated in different sectors of the healthcare system. Developing the surgical treatment is another major target, in order to lower the overall complication rate, without compromising the high cure rate of insulinomas.